Case Report: Resolution of remitting seronegative symmetrical synovitis with pitting edema during nivolumab therapy for gastric cancer - Ohmura, Hirofumi; Kondo, Moe; Uenomachi, Masato; Ariyama, Hiroshi; Ito, Mamoru; Tsuchihashi, Kenji; Ayano, Masahiro; Niiro, Hiroaki; Akashi, Koichi; Baba, Eishi (Frontiers in Oncology, 2023)
The anti-programmed cell death-1 (PD-1) antibody nivolumab has been shown to significantly prolong the survival of patients with unresectable advanced or recurrent gastric cancer (AGC). However, immune-related adverse events (irAEs), which show different profiles from those of cytotoxic agents or conventional molecular-targeted drugs including tyrosine kinase inhibitors, have been reported. Remitting seronegative symmetrical synovitis with pitting edema (RS3PE) is a rare autoimmune disorder with acute-onset, rheumatoid factor-negative, symmetric synovitis associated with limb edema observed in elderly persons. A case of RS3PE syndrome that developed after 2 administration of nivolumab for advanced gastric cancer is reported. This is the first report of a case of RS3PE syndrome as an irAE caused by nivolumab in a patient with gastric cancer.